Health workers’ knowledge and practices toward vaccine cold chain management and its associated factors in a resource-limited setting of Sheger, Oromia, Ethiopia: a multicenter cross-sectional study - Lucha Geneti; Seifadin Ahmed Shallo; Mecha Aboma Yebasa; Derese Bekele Daba (BMC Pediatrics)
Abstract Background Cold chain management is a continuous and cohesive process of preserving vaccines to ensure their availability and potency. However, the quality control of vaccines has been neglected in resource-limited areas such as Ethiopia. Adequate levels of health workers’ knowledge and practices in vaccine cold chain management are important to maintain the potency of vaccines and achieve the intended vaccine end goal. Objective To assess the level of knowledge and practices of health workers toward vaccine cold chain management and associated factors in resource-limited settings in Ethiopia. Methods An institution-based cross-sectional survey was conducted from May to June 2023 in eight sub-cities of Sheger City, Oromia Region, Ethiopia. 255 health workers were selected via simple random sampling from 17 health centers and 17 health posts. Data were collected through a self-administered questionnaire and entered in to EPI DATA version 3.1 and exported to SPSS version 26.0 software for analysis. Binary and multiple logistic regression analyses were carried out to identify factors associated with the knowledge and practices of health workers toward vaccine cold chain management. A variable with a p value < 0.25 was considered a candidate for further regression analysis, whereas a variable with a 95% CI and a p value < 0.05 was considered statistically significant. Result A total of 255 respondents participated, for a 100% response rate. The overall magnitude of good knowledge and practice of vaccine cold chain management was 58% (95% CI: 52.2%--64.3%) and 52.2% (95% CI: 46.3-58.4%), respectively. Receiving pre-service training (AOR = 8.2; 95% CI: (2.93–22.99), availability of SOP/guidelines (AOR = 6.55; 95% CI: (2.0–21.36) and receiving supportive supervision (AOR = 4.2; 95% CI: (1.67–10.59)) were significantly associated with good knowledge of cold chain management. The availability of SOP/guidelines (AOR = 2.13; 95% CI: (1.22–3.7)) and the knowledge of health workers (AOR = 2.32; 95% CI: (1.11–4.8) were significantly associated with good cold chain management practices. Conclusion There are gaps in knowledge and practice concerning cold chain management. There is an urgent need to improve the knowledge and practice of health workers in cold chain management in the newly organized but resource-limited administrative structure (Sheger) in Ethiopia.